1984
DOI: 10.3133/pp1400b
|View full text |Cite
|
Sign up to set email alerts
|

Geohydrology of the High Plains Aquifer in parts of Colorado, Kansas, Nebraska, New Mexico, Oklahoma, South Dakota, Texas, and Wyoming

Abstract: The High Plains aquifer, which underlies about 174,000 square miles in parts of eight States, is the principal source of water in one of the Nation's major agricultural areas. About 170,000 wells pump water from the aquifer to irrigate about 13 million acres in the High Plains. In 1978, the U.S. Geological Survey began a regional study of the High Plains aquifer to provide geohydrologic data and computer models of the aquifer needed to evaluate the effects of ground-water development. This report describes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(106 citation statements)
references
References 14 publications
0
99
0
Order By: Relevance
“…Gutentag et al . () reported that the specific yield of 76% of the aquifer is 10‐20%, although the values range from less than 5% to as much as 30%, but average 15.1%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gutentag et al . () reported that the specific yield of 76% of the aquifer is 10‐20%, although the values range from less than 5% to as much as 30%, but average 15.1%.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally recognized that recharge, if it exists at all, is limited in the Texas Panhandle (Gutentag et al ., ); however, some assert that there may be hydraulic interaction with the Dockum Group which underlies much of the Ogallala Aquifer in this region. For this to happen, the Dockum would need to have a greater head than the overlying aquifer, such as may occur in the confined portions in Deaf Smith County (Bradley and Kalaswad, ); however, they indicate that it is more likely that the Ogallala supplies the Dockum rather than vice versa.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The climate of the OAR is mostly semiarid, with a distinct east‐west gradient in average annual precipitation ranging from 400 mm in the west to 800 mm in the east with a clear south‐north slope in mean annual pan evaporation from 2,700 mm in the south to 1,500 mm in the north (Gutentag et al ; Shafer et al ). With low precipitation and high pan evaporation, agriculture in the OAR is heavily dependent on irrigation with more than 95% of the water extracted from the Ogallala Aquifer used for crop production.…”
Section: Introductionmentioning
confidence: 99%